2013
DOI: 10.4103/2319-4170.113854
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of visual outcomes and complications following levator resection for unilateral congenital blepharoptosis without strabismus

Abstract: The levator resection provides satisfactory results both in function and cosmesis in patients with unilateral congenital blepharoptosis. Amblyogenic ametropia is the leading cause of amblyopia in the patients with unilateral isolated congenital blepharoptosis. However, patients with unilateral congenital blepharoptosis should have cycloplegic refraction as early as possible, and their visual status monitored until visual maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Conversely, waiting to perform surgical correction at an older age allows patients to be more cooperative with examinations, producing better anatomical results and refractive stability. Wu et al 11 reported that there was no signi cant visual bene t from surgical correction of congenital ptosis in patients at 2 years or younger, compared with patients operated upon between 2 to 5 years of age. Based on a retrospective chart review of 62 patients, Cadera et al 12 reported that changes in cylinder were not statistically signi cant between patients in their younger and older-age groups (< 4 years old and ≥ 4 years old, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, waiting to perform surgical correction at an older age allows patients to be more cooperative with examinations, producing better anatomical results and refractive stability. Wu et al 11 reported that there was no signi cant visual bene t from surgical correction of congenital ptosis in patients at 2 years or younger, compared with patients operated upon between 2 to 5 years of age. Based on a retrospective chart review of 62 patients, Cadera et al 12 reported that changes in cylinder were not statistically signi cant between patients in their younger and older-age groups (< 4 years old and ≥ 4 years old, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Wu et all. 20 , levator resection was performed in 84 children who had unilateral congenital ptosis and surgical success rate was reported as 84.5%. Another study from Iran, Abrishamiet all.…”
Section: Discussionmentioning
confidence: 99%
“…Levator muscle resection is a standard procedure for ptosis correction and a good Bell`s phenomenon is a pre- requisite for ptosis surgery [4, 5]. Post- operative rehabilitation depends on the recovery of Bell`s phenomenon and varies from patient to patient.…”
Section: Introductionmentioning
confidence: 99%